BCL11A enhancer dissection by Cas9-mediated in situ saturating mutagenesis - Canver, Matthew C. (Nature, 2015)
Enhancers, critical determinants of cellular identity, are commonly identified by correlative chromatin marks and gain-of-function potential, though only loss-of-function studies can demonstrate their requirement in the native genomic context. Previously we identified an erythroid enhancer of BCL11A, subject to common genetic variation associated with fetal hemoglobin (HbF) level, whose mouse ortholog is necessary for erythroid BCL11A expression. Here we develop pooled CRISPR-Cas9 guide RNA libraries to perform in situ saturating mutagenesis of the human and mouse enhancers. This approach reveals critical minimal features and discrete vulnerabilities of these enhancers. Despite conserved function of the composite enhancers, their architecture diverges. The crucial human sequences appear primate-specific. Through editing of primary human progenitors and mouse transgenesis, we validate the BCL11A erythroid enhancer as a target for HbF reinduction. The detailed enhancer map will inform therapeutic genome editing. The screening approach described here is generally applicable to functional interrogation of noncoding genomic elements.